Do Income Smoothing Practices Explain the Lower Earnings-Price Ratio of Japanese Firms Compared to Those of the U.S. Firms? - Kusuma, Indra Wijaya (Gadjah Mada International Journal of Business, 2005)
This study examines the variation in earnings-price ratios across Japanese and U.S. firms. The earnings-price ratio is one of the indicators often used by investors to determine their trading strategy. Previous literature document that Japanese firms have consistently lower earnings-price ratios than U.S. firms even though the earnings of Japanese firms have been adjusted to the U.S. GAAP. The objective of this study is to show that Japanese firms engage in income smoothing practices that stabilize earnings, thereby increasing Japanese investorsâ willingness to pay higher prices for Japanese stocks. Comparing the income smoothing index and proportion of firms identified as smoothers shows that the intensity of Japanese firms practicing income-smoothing is greater than that of U.S. firms. The results also show that income-smoothing index is significant in explaining the cross-sectional variation of earnings-price ratios for Japanese firms but it is not significant for U.S. firms.Â  Two potential explanations for the results of U.S. firms are as follows.Â  First, income smoothing is not practiced widely across firms in the U.S.Â  Therefore, the variation of income smoothing does not explain the variation in the cross-sectional earnings-price ratios.Â  Second, even if U.S. firms practice income smoothing, the investors are aware of it and do not take earnings figures literally.Another results show that controlling for income smoothing does not eliminate the differences in the earnings-price ratios of the Japanese and U.S. firms. It is appropriate to conclude that although income smoothing plays a role in explaining the variations of earnings-price ratios across Japanese firms, it is not the only factor that contributes to the differences in the earnings-price ratios of Japanese and U.S. firms.Â  Other factors may play a role which are either country-specific (such as inflationary expectations, tax regimes) or firm-specific (such as quality of earnings, real returns) as suggested by Brown (1989). The overall results are consistent across samples.